Cardiac resynchronization therapy (CRT) nonresponders in the contemporary era: A state-of-the-art review - Gerra, Luigi; Bonini, Niccolò; Mei, Davide Antonio; Imberti, Jacopo Francesco; Vitolo, Marco; Bucci, Tommaso; Boriani, Giuseppe; Lip, Gregory Y H (Heart rhythm, 2025)
In the 2000s, cardiac resynchronization therapy (CRT) became a revolutionary treatment for heart failure with reduced left ventricular ejection fraction (HFrEF) and wide QRS. However, about one-third of CRT recipients do not show a favorable response. This review of the current literature aims to better define the concept of CRT response/nonresponse. The diagnosis of CRT nonresponder should be viewed as a continuum, and it cannot rely solely on a single parameter. Moreover, baseline features of some patients might predict an unfavorable response. A strong collaboration between heart failure specialists and electrophysiologists is key to overcoming this challenge with multiple strategies. In the contemporary era, new pacing modalities, such as His-bundle pacing and left bundle branch area pacing, represent a promising alternative to CRT. Observational studies have demonstrated their potential; however, several limitations should be addressed. Large randomized controlled trials are needed to prove their efficacy in HFrEF with electromechanical dyssynchrony.